A framework for resolving task overload problems using intelligent software agents - Itaiwi A.-M.K.; Ahmad M.S.; Hamid N.H.A.; Jaafar N.H.; Mahmoud M.A. (2023)
In this paper, we model task delegation to resolve task overload problems using intelligent software agents in a normative environment. In such environment, where humans are responsible for various tasks, which are not transparent to others except to the management, task delegation is one of the possible solutions. In order to effectively delegate roles and tasks, the delegator must comply with certain norms and rules to avoid delays in completing the tasks. In this paper, we explore the complexity of decision making process in multi-level hierarchical organization and apply delegation rules to resolve issues relating to task overload problem. We then develop a framework using intelligent software agents to resolve the problem. 2011 IEEE.